Konsep Distribusi Kepemilikan dalam Islam - Amir Salim (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2019)
The background of this research is that God tells humanity to make their contribution to people in need. Wealth that must be managed and distributed to the community and wealth should not only be concentrated in certain groups. Wealth that is only centered on certain groups will hamper economic growth because this cannot be utilized as well as possible and eventually cause community opposition. According to the Islamic economic system, distribution is obtained through data sources obtained from Islamic economic system books, literature, and relevant study materials. Ownership in the concept of Islam, what is in the universe belongs only to Allah. Humans as a trusted caliph to be approved by the universe.